Atomic Structure and Electrical Activity of Grain Boundaries and Ruddlesden–Popper Faults in Cesium Lead Bromide Perovskite. Issue 4 (3rd December 2018) - Thind, Arashdeep Singh; Luo, Guangfu; Hachtel, Jordan A.; Morrell, Maria V.; Cho, Sung Beom; Borisevich, Albina Y.; Idrobo, Juan‐Carlos; Xing, Yangchuan; Mishra, Rohan
Abstract: To evaluate the role of planar defects in lead‐halide perovskites—cheap, versatile semiconducting materials—it is critical to examine their structure, including defects, at the atomic scale and develop a detailed understanding of their impact on electronic properties. In this study, postsynthesis nanocrystal fusion, aberration‐corrected scanning transmission electron microscopy, and first‐principles calculations are combined to study the nature of different planar defects formed in CsPbBr3 nanocrystals. Two types of prevalent planar defects from atomic resolution imaging are observed: previously unreported Br‐rich [001](210)∑5 grain boundaries (GBs) and Ruddlesden–Popper (RP) planar faults. The first‐principles calculations reveal that neither of these planar faults induce deep defect levels, but their Br‐deficient counterparts do. It is found that the ∑5 GB repels electrons and attracts holes, similar to an n–p–n junction, and the RP planar defects repel both electrons and holes, similar to a semiconductor–insulator–semiconductor junction. Finally, the potential applications of these findings and their implications to understand the planar defects in organic–inorganic lead‐halide perovskites that have led to solar cells with extremely high photoconversion efficiencies are discussed. Abstract : The atomic structure and electronic properties of Ruddlesden–Popper (RP) faults and grain boundaries (GBs) in CsPbBr3 are revealed using electron microscopy and density functional theory calculations. The halide concentration at these planar defects is found to be crucial to their electronic properties. The GBs are predicted to repel electrons and attract holes, whereas the RP faults repel both.